Experimental Research on the Vibration of Ship Propulsion Shaft under Hull Deformation Excitations on Bearings - Cong Zhang; Dongchen Xie; Qianwen Huang; Zhihua Wang (Shock and Vibration)
With the development of ship enlargement, the problems of coupling vibration between hull and propulsion system and vibration transmission via bearings are more and more prominent. Based on the theory of shaft vibration and the experimental system for dynamic characteristics of the shaft, an experiment plan about propulsion shaft vibration under dynamic excitations is designed in this paper. The performance of propulsion shaft vibration under hull deformation excitations applied on intermediate and stern bearings is studied. Hydraulic excitations in horizontal and vertical directions on the intermediate bearing and stern bearing of the experimental model of propulsion shaft are considered in this paper to simulate hull deformation on bearings of the ship. Vibration characteristics of the shaft under different excitations are gained and coupling effects are discussed. Moreover, the influences of amplitude and direction of excitations on bearings and the shaft rotation speed on the vibration of propulsion are studied. The results show that aiming at improving the safety and reliability of navigation, the hull deformation, especially the horizontal hull deformation excitation on the intermediate bearing, is not neglectable and should be considered during primary design. Also, rotation speed and resonant frequency are needed to be well designed with the frequencies of hull deformation excitations.